NILAI-NILAI PENDIDIKAN ISLAM DALAM KELUARGA BUGIS - K, ABD. RAHMAN (P3M STAIN Parepare, 2014)
Teaching material contains a lot of people Buginese values of moral education which when translated include the value of moral education to Allah, the value of moral education to the Prophet Muhammad Saw, The value of the personal moral education, family value sakhlah education, moral education in social values, and the value moral education in the state that aims to helppeople become tautongeng process (human who complete/perfect man) who is the educational goals of the Bugis.Bugis society especially in Pinrang pay great attention to the cultivation of values education in her daily life. Although the value of education and other laudable traits (character) of the child is not fully carried out on the basis of religious orders but rather on the basis of inherited liabilities of social norms, but we realize it or not, many parents have instilled the values of education that is consistent with the teachings of Islam towards their children. Values of Islamic education include: The values of the personal moral education, values of Islam, especially moral education in the family that includes and values moral education in social relationships.